Does digitalization drive corporate green transformation?—Based on evidence from Chinese listed companies - Peng, Cheng; Jia, Xinyuan; Zou, Yu (Frontiers in Environmental Science, 2022)
Accelerating the digital transformation of enterprises, enabling enterprise operation and management with digitalization, and driving green transformation are important tasks to further promote the digital construction of a country. Based on the text data mining method, this paper investigates digitalization’s impact on enterprises’ green transformation and its mechanisms, using A-share listed companies in Shanghai and Shenzhen as research samples from 2011 to 2020. The results show that digitalization has the effect of “inhibiting” and then “promoting” on the green transformation of enterprises, i.e., the relationship between the two is U-shaped. The heterogeneity analysis shows that this U-shaped relationship exists among non-heavy polluting enterprises, eastern enterprises, main-board enterprises, GEM enterprises, and enterprises with high digitization speed. As far the influence mechanism, the dynamic capability acts as a partial mediator in the relationship between digitalization and green transformation. This study provides a useful reference for enterprises to drive sustainable development and promote the construction of national ecological civilization.